Formative Assessment Implementation: Does it Enhance EFL Students’ Learning Motivation? - Salsabila Artristiyani Summa Ekasuci; Siti Lestari; Raveenthiran Vivekanantharasa (Universitas PGRI Semarang, 2024)
This study aims to determine the implementation of formative assessment in English teaching to enhance student motivation. The research design of this study is a qualitative descriptive research design. The subjects in this research were 30 class X students at SMA Indonesia Semarang. The instruments used in this research were observation, interviews, and open and closed questionnaires adopted and adapted from Theodoridis & Kraemer (2020). The collected data was then analyzed using descriptive qualitative and closed questionnaires using SPSS 21. The research showed that before implementing formative assessments such as quizzes, discussions, and Google forms in learning English, students experienced various obstacles, including lack of vocabulary, understanding, self-confidence, etc. However, everything changes when this type of assessment is implemented where students show significant results as seen from students being able to understand the learning, increasing students' vocabulary in speaking English, making learning more interesting and not boring. From the above, it can be said that students are very motivated which shows a result of 82.1% in this research.